2006
DOI: 10.1203/01.pdr.0000219129.12960.c2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Bone Metabolism In Children Treated for Bone Sarcomas

Abstract: ABSTRACT:In adolescent bone sarcoma patients, bone mass acquisition is potentially compromised at a time in which it should be at a maximum. To evaluate the problem we measured bone mineral density (BMD) and serum markers of bone formation and resorption in a series of pediatric patients with bone tumors. BMD was measured by dual-energy x-ray absorptiometry, at clinical remission, for lumbar spine and the neck of the femur in 38 osteosarcoma and 25 Ewing's sarcoma patients. Mean age was 20.65 and 19.13 y respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 32 publications
6
48
2
1
Order By: Relevance
“…This was known for patients with postmenopausal osteoporosis [29] and sarcoma [40], and also applies to young survivors of Ewing tumors. In line with Ruza et al [34], in patients with Ewing tumors, BMI positively correlated with low BMD. Therefore BMI may be an indicator for assessing BMD in survivors of bone tumors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This was known for patients with postmenopausal osteoporosis [29] and sarcoma [40], and also applies to young survivors of Ewing tumors. In line with Ruza et al [34], in patients with Ewing tumors, BMI positively correlated with low BMD. Therefore BMI may be an indicator for assessing BMD in survivors of bone tumors.…”
Section: Discussionsupporting
confidence: 87%
“…During the period of bone accumulation in childhood and adolescence, a malignant tumor and its treatment can affect bone turnover and decrease bone mineral density (BMD) [18]. Reduced levels of BMD were reported in long-term survivors of childhood cancers, such as leukemia [2,17], osteosarcoma [18], and a few mixed solid pediatric tumor cohorts [3,26,30,32,34]. Therefore, in survivors of Ewing tumors, an accumulation of treatment-induced effects may compromise bone [3,25].…”
Section: Introductionmentioning
confidence: 99%
“…HD-MTX, a standard agent in osteosarcoma protocols, reportedly has reduced BMD [8,17]. The literature, however, shows decreased BMD in patients with Ewing's sarcoma treated without HD-MTX [33]. Thus, it is unclear whether osteoporosis after chemotherapy relates to HD-MTX or to other factors.…”
Section: Discussionmentioning
confidence: 99%
“…We also compared our data with that in the literature ( Table 7). The studies varied in study population and followup times; nevertheless, both revealed a remarkable number of patients with BMD reduction and fractures [17,33], which are often the first indicator of bone loss. The estimated lifetime-fracture risk attributable to osteoporosis reportedly is exponentially related to BMD, which decreases up to 10-fold faster if related to tumor treatment, especially in association with hypogonadism [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation